Diagnosis of congenital and infantile nephrotic syndromes in renal biopsies in Minas Gerais, Brazil: Six case reports. (1st November 2016) - Rocha, Laura Penna; Custódio, Fabiano Bichuette; Machado, Juliana Reis; de Morais Pereira, Lívia Helena; Monteiro, Maria Luiza Gonçalves dos Reis; Laterza, Valéria Lima; dos Reis, Marlene Antônia; Corrêa, Rosana Rosa Miranda
ABSTRACT: Congenital or infantile nephrotic syndromes (CNS/INS) correspond to a heterogeneous group of rare diseases in which glomerular renal dysfunction and proteinuria are prominent. The aim of this study is to present six cases of possible CNS/INS with diagnoses based on clinical findings and especially histological, ultrastructural, and immunohistochemical characteristics of renal biopsies. Four cases are presented with diffuse mesangial sclerosis, one of them possibly part of Denys–Drash syndrome and two cases with CNS probably of the Finnish type in patients between 3 months old and 13 years old. The study focuses on the late evolution of Denys–Drash syndrome to end-stage renal disease in a 13-year-old patient and the diagnosis of diffuse mesangial sclerosis in an 8-year-old patient. Thus, it contributes to a better epidemiological characterization of these syndromes, demonstrating cases of CNS/INS in infrequent age groups.